CHARACTERIZATION IN THE PORTRAYAL OF BULLYING IN THE CHILDREN'S BOOK ENTITLED "LLAMA LLAMA AND THE BULLY GOAT" (2013) - Nur Assyifa, - (2021)
The present study entitled Characterization in the Portrayal of Bullying in the Children's Book Entitled "Llama Llama and the Bully Goat" (2013) aims to investigate how bullying is portrayed and the way meanings are constructed in the chosen book. The study employs a qualitative approach with textual analysis since this study focuses on bullying incidents in the text. This study is framed by theory of character (Klarer, 1999) and characterization (Reams, 2015) to achieve the aims. The study found that the portrayal of bullying is developed from characterization in different types of bullying context. Furthermore, to strengthen the portrayal of bullying in the book, direct and indirect characterization are also used to explore characters' bullying in their bullying experiences. In the study, the characterization of the bully indicates an imbalance of power which is affected by the presence or absence of adults. The book implies the significant role of adults in bullying cases among children. Keywords: Bullying, Character, Characterization